Hearing voices - anthrogogies of politics in psychiatric rehabilitation - Clubbs Coldron, Benjamin (2021)
In this thesis I investigate how policies aiming to enhance and increase opportunities for political participation for people with mental disabilities are currently being implemented in residential psychiatric rehabilitation. These practices form part of the implementation of the United Nations Convention of the Rights for Persons with Disabilities (UNCRPD) article 29 – the right to equal opportunities to participate in public and political life.